About uniformly Lindelöf spaces - Bekbolot E. Kanetov; Ulukbek A. Saktanov; Meerim O. Zhanakunova (E-Journal of Analysis and Applied Mathematics)
The idea of Lindelöfness is one of the most important in General Topology. There have been some variants in defining uniformly Lindelöfness of uniform spaces. For example, uniform A-Lindelöfness in the sense of L.V. Aparina [1], uniform B-Lindelöfness in the sense of A.A. Borubaev [2], uniform I-Lindelöfness in the sense of D.R. Isbell [5]. In this paper we propose a new approach to the definition of a uniform analogue of Lindelöfness. We introduce and study uniformly Lindelöf spaces.